2023
DOI: 10.3390/ijerph20116050
|View full text |Cite
|
Sign up to set email alerts
|

Parent Experiences in the NICU and Transition to Home

Abstract: Families (n = 12) with infants born at <29 weeks gestation shared their experiences while in the NICU and transitioning home. Parents were interviewed 6–8 weeks after NICU discharge, including some during the acute phase of the COVID-19 pandemic. Findings regarding the parent experience in the NICU were focused around challenges navigating parent-infant separation, social isolation, communication difficulties, limited knowledge of preterm infants, mental health challenges. Parents also discussed supports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…The analysis indicates that the incapacity to participate in caregiving routines can result in a lack of parental self-efficacy and bonding issues. 17 In our study, parents made similar statements.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The analysis indicates that the incapacity to participate in caregiving routines can result in a lack of parental self-efficacy and bonding issues. 17 In our study, parents made similar statements.…”
Section: Discussionsupporting
confidence: 73%
“…For example, early discharge programmes aim to foster family unity and promote infant development and the well-being of both parents and the infant. 3,11,17 Previous studies on the impact of NICU admission on parents have shown that the emotional and physical detachment experienced during the hospital stay exacerbates difficulties in transitioning to a home environment. Spence et al reported that parents reported sentiments of grief concerning the temporal separation from their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, NICU discharge and the transition to home, while joyous, has also been described by families to be sudden and anxiety-provoking 34 . Not only do families feel the pressure of now caring for their previously unwell infant in the home, but readmission rates of NICU graduates are, in fact, higher than their term counterparts 35 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Expansion of long-term follow-up services and including other services in and out of the NICU, such as early developmental intervention, mental health services, support groups, and other essential services, might offer needed care to NICU graduates and their families [18]. Environmental changes in the NICU related to noise, light, and humidity are incorporated to avoid any possible stress that may hamper the child's development [1].…”
Section: Continued Service Support and Other Relevant Servicesmentioning
confidence: 99%